2014
DOI: 10.2169/internalmedicine.53.2386
|View full text |Cite
|
Sign up to set email alerts
|

Human Intestinal Spirochaetosis in Two Ulcerative Colitis Patients

Abstract: A histological examination of colonic biopsies of the longitudinal and irregularly-shaped ulcerative lesions of a 37-year-old man and 61-year-old man with ulcerative colitis showed so-called "fringe formation," a typical finding of Brachyspira infection. The antibody titer to Brachyspira aalborgi showed marked elevation in both cases, and the patients were each treated with 1,000 mg of metronidazole for 14 days. Colonoscopy performed after treatment showed an improvement in the ulcerative lesions in both patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…(15) We also have reported cases of HIS infection in ulcerative colitis patients undergoing long-term steroid therapy. (16)…”
Section: Discussionmentioning
confidence: 99%
“…(15) We also have reported cases of HIS infection in ulcerative colitis patients undergoing long-term steroid therapy. (16)…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammation did not seem to be associated with HIS, a HIS case was found among the UC cases, representing 12.5 % of UC cases in the present study. Previous studies have reported finding HIS among UC cases, and some HIS cases might mimic the clinical, endoscopic, and pathologic features of UC [13][14][15]. Considering the clinical importance of UC, the possible association between HIS and UC should be a subject for continued scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, most cases are found incidentally by histological examination of specimens taken endoscopically during (a) annual check-up in healthy persons, (b) further investigation after positive results for fecal occult blood, or (c) follow-up after polypectomy/surgery for tumorous lesions [2]. However, some HIS cases manifest a signi cant degree of mucosal in ammation [4,5] or exacerbated in ammaton of accompanying ulcerative colitis [6], and thus the pathogenesis of HIS is considered uncertain. Histologically, mucosal in ammation in HIS has been reported to be mild or non-speci c [1], but mucosal eosinophilia was indicated in a recent report [7].…”
Section: Introductionmentioning
confidence: 99%